Penerapan Integrasi Metode AHP dan Entropy dalam Pengambilan Keputusan Seleksi Beasiswa Perguruan Tinggi - Permadi, Yuda; Saprudin, Saprudin; Rosyani, Perani (Bulletin of Computer Science Research, 2025)
Multi-criteria decision making (MCDM) is a complex process involving multiple criteria with different levels of importance. One of the most critical aspects of MCDM is the determination of criterion weights, as inappropriate weighting may lead to biased and unrepresentative decision outcomes. This study aims to apply an integrated weighting approach using the Analytic Hierarchy Process (AHP) and the Entropy method in multi-criteria decision making. The research employs a case study of scholarship recipient selection at University X, using decision data consisting of five student alternatives and four evaluation criteria, namely Grade Point Average (GPA), parents’ income, organizational activities, and essay assessment. The AHP method is used to derive subjective weights based on decision-makers’ preferences, while the Entropy method is applied to obtain objective weights based on data variability. Weight integration is performed using the arithmetic mean approach to produce final weights that balance subjective judgment and objective information. The results indicate that the integrated AHP–Entropy weights produce a more balanced distribution compared to single-method weighting. Weight stability is evaluated through comparative analysis of weight variations across methods, demonstrating that the integration reduces subjective dominance and enhances the representation of objective data characteristics. Therefore, the integration of AHP and Entropy is proven to be an effective weighting approach for multi-criteria decision making, particularly in the context of scholarship selection in higher education institutions.